ĐIỀU CHỈNH PHÁP LUẬT THUẾ CHỐNG CHUYÊN GIA CỦA TRUNG QUỐC ĐỐI VỚI CÁC CÔNG TY ĐA QUỐC GIA - Phát, Nguyễn Tấn (Tạp chí Khoa học Đại học Cần Thơ, 2004)
Abstract Chinais one of the largest recipients of foreign investment capital in recent years. Particularly in the year 2003,Chinais the largest recipient of foreign investment capital in the world with total capital of US$ 52 billion. Foreign investment capital plays an important role in the development of Chinese national economy and helps to adjust the domestic economic structure towards regional and international integration. However, through activities of investment, production, business, certain multinational enterprises have avoided or reduced obligations of paying corporate income tax in China through transfer pricing policies (non- arm?s length prices). The consequence is that the Chinese Government loses tax revenue. To regulate and manage transfer pricing policies of multinational enterprises,Chinahas enacted and enforced transfer pricing laws. Transfer pricing policies of multinational enterprises and transfer pricing laws are very new matters, along with the increase of foreign investment capital and the opening process inVietnam. However,Vietnamlacks of sufficient regulations and experiences on these matters. Since China has similar polity, economy, and culture with Vietnam and has handled this matter successfully, it is useful to find out how Chinese tax authority control and administer transfer pricing policies of multinational enterprises arising from foreign investment. This article examines systematically Chinese transfer pricing laws. Firstly, the article will introduce an overview of the development of Chinese transfer pricing laws. It will then discusses and analyses the arm?s length price, the scope of application of transfer pricing laws, the methods of establishing arm?s length price, documentation requirements, penalties and conclusive remarks. Key words: transfer pricing, associated enterprises, arm?s length price, methods of establishing arm?s length price, documentation requirements and penalties Title: Stipulating chinese tax laws on transfer pricing for multinational enterprises